Culture and power in traditional Siamese government - Englehart, Neil A., 1964- (Ithaca, N.Y. : Southeast Asia Program Publications, Southeast Asia Program, Cornell University, 2001)
A broad reevaluation of Siam's political culture as it existed prior to King Chulalongkorn's administrative reforms in the nineteenth century. Englehart offers evidence to show that traditional Siamese government functioned more effectively and rationally than most scholars have acknowledged.
Frontmatter -- Contents -- Acknowledgments -- Preface -- Chapter 1: Introduction -- Chapter 2: Social And Cultural Context -- Chapter 3: Political Institutions At The Grassroots -- Chapter 4: Political Institutions: Provincial And Central Government -- Chapter 5: Conceptual Change And Institutional Innovation -- Chapter 6: Conclusion: Culture And Power In A Comparative Perspective -- Appendix I: Varieties Of Nai And Phrai -- Appendix II Reign Dates Of Kings Mentioned In The Text -- Bibliography
Includes bibliographical references (pages 117-130).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Thailand -- Politics and government -- 19th century; Political culture -- Thailand; Thaïlande -- Politique et gouvernement -- 19e siècle.; HISTORY -- Asia -- Southeast Asia; POLITICAL SCIENCE -- History & Theory; Political culture; Politics and government; Thailand; Culture politique -- Thaïlande.; Thaïlande -- Politique et gouvernement -- 19e siècle.; 1800-1899